Submarine Psychology: A South African Perspective on Assessing Readiness after Adversity - Van Wijk, Charles (Scientia Militaria - South African Journal of Military Studies, 2025)
Psychological readiness is a critical component for the success of the mission of the South African Navy, as well as the wellbeing of their personnel. The study on which this article reports, explored psychological readiness within the unique and demanding context of submarine duty. Key psychological factors for readiness include good clinical mental health, adaptability, and effective interfacing with support systems. From the 1970s, SA military psychologists have been involved in the selection of submariners, focusing on traits, such as motivation, intelligence, interpersonal skills, and personality. More recently, positive psychological constructs, such as sense of coherence, psychological hardiness, and mental toughness, were also identified as important for coping with the isolation and stress inherent in submarine operations. The current research specifically examined the aftermath of the SAS Manthatisi accident of September 2023, highlighting the psychological resilience of submariners and risk and protective factors associated with their post-accident adaptation. Initial screenings showed the presence of adjustment difficulties and other mental health challenges, but by seven months, most submariners had returned to their baseline mental health, demonstrating resilience and effective coping strategies. The importance of thorough pre-service selection, regular psychological screening, and timely interventions were emphasised as key to maintaining operational readiness. Insights from the accident furthermore underlined the need for resilient personnel who can withstand adverse events and speedily return to duty. The study concluded that ongoing availability of psychological support and the cultivation of resilience and adaptability are essential for maintaining the readiness and effectiveness of submariners.